2017
DOI: 10.1177/0895904817719516
|View full text |Cite
|
Sign up to set email alerts
|

Interest Group Activity in the Context of Common Core Implementation

Abstract: This article analyzes the messages and strategies of a sample of education interest groups, and assesses their interpretations of the political context to understand how the Common Core State Standards (CCSS) lost both political and public support during the crucial period of 2013-2014. Based on interviews with representatives of 19 interest groups who were actively involved in communicating about the standards, it focuses on the arguments, communication strategies, and targeted audiences of professional advoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Many critical perspectives, over decades, coalesce on a number of key issues such as the reproductive role that schools play in: ensuring the transmission of dominant ideologies and forms of knowledge and the distribution of skills that ensure that social division and patterns of privilege are maintained (Giroux, 2019 ). Schools in essence function as agencies of social and cultural reproduction (Bourdieu, 1990 ; Lampert, 2016 ; Laureau & Goyette, 2014 ; Reay, 2006 , 2018 ; Reay et al, 2007 , 2011 ) and schooling is a series of preparatory experiences that set many groups of children and young people up for unequal futures (Apple, 2012 ; Supovitz & McGinn, 2019 ; Thomson, 2007 ; Willis, 1977 ). Schools and the process of schooling therein are exposed as institutions that individualize failure and the responsibility for failure (Labaree, 2012 ; Paredes Scribner & Fernández, 2017 ; Reay, 2018 ; Thomson et al, 2012 ; Wrigley, 2012 ).…”
Section: The Problem: Why the Need For New Learning Environments?mentioning
confidence: 99%
“…Many critical perspectives, over decades, coalesce on a number of key issues such as the reproductive role that schools play in: ensuring the transmission of dominant ideologies and forms of knowledge and the distribution of skills that ensure that social division and patterns of privilege are maintained (Giroux, 2019 ). Schools in essence function as agencies of social and cultural reproduction (Bourdieu, 1990 ; Lampert, 2016 ; Laureau & Goyette, 2014 ; Reay, 2006 , 2018 ; Reay et al, 2007 , 2011 ) and schooling is a series of preparatory experiences that set many groups of children and young people up for unequal futures (Apple, 2012 ; Supovitz & McGinn, 2019 ; Thomson, 2007 ; Willis, 1977 ). Schools and the process of schooling therein are exposed as institutions that individualize failure and the responsibility for failure (Labaree, 2012 ; Paredes Scribner & Fernández, 2017 ; Reay, 2018 ; Thomson et al, 2012 ; Wrigley, 2012 ).…”
Section: The Problem: Why the Need For New Learning Environments?mentioning
confidence: 99%
“…Initially adopted in 2010 by 46 states, the CCSS became increasingly controversial, with several states backing out and replacing or revising the CCSS. Opponents of the CCSS made a range of arguments that critiqued the Standards themselves (e.g., not developmentally appropriate, attended to academic priorities at the expense of social and emotional needs), but primarily attacked the CCSS on cultural and ideological grounds (e.g., federal overreach, data privacy, corporate profiting from a public good; Supovitz & McGuinn, 2017).…”
Section: National Factors Contributing To Opting Out Of New Jersey State Testingmentioning
confidence: 99%
“…They found that both the overall sentiment, and that of opinion leaders, was overwhelmingly negative toward the CCSS. Supovitz and McGuinn (2017) conducted interviews with 19 education advocacy groups that supported the CCSS in late 2013 and early 2014 and analyzed their communication strategies. They found that their web-based media strategies focused on toolkits and guides with only a thin social media presence, "based on a mistaken belief that Common Core supporters felt that information campaigns would be enough to clarify the benefits of the standards" (p. 24).…”
Section: Research Questionsmentioning
confidence: 99%
“…An emerging body of research has also begun exploring advocacy organizations' use of social media (Bortree & Seltzer, 2009;Edwards & Hoefer, 2010;Greenberg & MacAulay, 2009;Supovitz & McGuinn, 2017;Supovitz et al, 2018). Because social media is more personalized, messages can be targeted, potentially broadening advocacy participation (Bennett, 2012).…”
mentioning
confidence: 99%